Practicalities of participation in urban IWRM: perspectives of wastewater management in two cities in Sri Lanka and Bangladesh - Evans, Alexandra E.V.; Varma, Samyuktha (2009)
As the demand for water in cities increases, the quantity of wastewater being produced is growing at a phenomenal rate. If resources are to be managed effectively, a new paradigm is required for urban wastewater management. This paper reviews the initial findings of a participatory action planning process for managing wastewater for agricultural use. It finds that such processes need considerable facilitation, capacity building and knowledge sharing, but that if a plan can be devised that meets the needs of the stakeholders, even if some compromise is required, then certain stakeholders are likely to take responsibility for specific aspects. This may not meet the entire integrated water resources management (IWRM) vision of the plan but provided the plan is developed in such a way that incremental implementation will be beneficial then this will produce some success and may stimulate further cooperation.